ANALISIS KEAKTIFAN BELAJAR MELALUI MODEL PROJECT BASED LEARNING (PJBL) PADA PEMBELAJARAN IPAS DI SEKOLAH DASAR - Lainun Nafisyah; Yuni Ratnasari; Eka Zuliana; Yunfia Nabella; Lufita Devi Rahmawati; Siti Farida Inayati (Institut Daarul Qur'an Jakarta, Indonesia, 2026)
This study was conducted to address the low level of student learning activeness in IPAS learning on the topic of atmospheric layers in Grade V at SD 6 Gondangmanis. Based on preliminary observations, only 2 out of 6 students actively participated in the learning process, while the remaining 4 students tended to be passive during classroom activities. The purpose of this study was to describe students' learning activeness through the implementation of the Project Based Learning (PjBL) model in IPAS learning on the topic of atmospheric layers. The study employed a qualitative approach with a case study design The participants of this study were six Grade V students of SD 6 Gondangmanis. Data were gathered through observations, interviews, and documentation. The collected data were analyzed using the Miles and Huberman interactive analysis model, which consists of data reduction, data presentation, and conclusion drawing. The findings indicate that students' learning activeness was reflected in their participation in asking and answering questions, engaging in discussions, collaborating in groups, completing project tasks, and presenting project results. Project-based learning also created a collaborative learning environment and provided students with opportunities to be directly involved in the learning process. The study concludes that the Project Based Learning model facilitates the emergence of various forms of student learning activeness in IPAS learning on the topic of atmospheric layers in elementary school.